Family Resilience Through Financial Literacy Within the Framework of Integrating Social Sciences and the Concept of the Prophet's Hadith - Ali, Muhammad; Ali Amiruddin, Andi Muhammad; Ahmad, La Ode Ismail; Fatmal, Abd. Bashir; Handayani, Dian (El-Usrah: Jurnal Hukum Keluarga, 2026)
Family Resilience has gained increasing scholarly attention amid growing economic uncertainty and financial vulnerability. This study aims to reconceptualize financial literacy as a pillar of family resilience from a Hadith perspective, addressing a gap in mainstream literature that often overlooks ethical and religious foundations. This research uses an interpretative qualitative method, analyzed using an integration-interconnection approach by Amin Abdullah, namely analyzing the Prophet's hadiths regarding household financial management, then integrating them with social sciences, such as economics and finance, and Islamic law. The findings demonstrate a strong convergence between prophetic ethical principles and core indicators of modern financial literacy. The Hadith emphasis on responsibility for family provision aligns with budgeting practices and prioritization of essential needs, thereby supporting household economic stability. Teachings on moderation in consumption foster adaptive and sustainable financial attitudes, contributing to long-term resilience. Prophetic warnings against excessive debt reflect an early awareness of structural financial risks that contemporary studies associate with family stress, conflict, and economic fragility. Furthermore, ethical guidance on the use of wealth cultivates value-oriented financial behavior that enhances not only economic resilience but also social, emotional, and moral well-being within households. Overall, the study shows that Hadith-based financial literacy operates as a moral–financial capability that integrates technical financial competence with ethical responsibility. Thus, this research strengthens the theory of integration-interconnection of hadith studies with social sciences, especially economics and Islamic family law, which offers a conceptual basis for the development of family policies and contextual and sustainable financial literacy education.